Molecular dynamics simulations informed by membrane lipidomics reveal the structure–interaction relationship of polymyxins with the lipid A-based outer membrane of Acinetobacter baumannii. (10th September 2020) - Jiang, Xukai; Yang, Kai; Yuan, Bing; Han, Meiling; Zhu, Yan; Roberts, Kade D; Patil, Nitin A; Li, Jingliang; Gong, Bin; Hancock, Robert E W; Velkov, Tony; Schreiber, Falk; et al.
Abstract: Background: MDR bacteria represent an urgent threat to human health globally. Polymyxins are a last-line therapy against life-threatening Gram-negative 'superbugs', including Acinetobacter baumannii . Polymyxins exert antimicrobial activity primarily via permeabilizing the bacterial outer membrane (OM); however, the mechanism of interaction between polymyxins and the OM remains unclear at the atomic level. Methods: We constructed a lipid A-based OM model of A. baumannii using quantitative membrane lipidomics data and employed all-atom molecular dynamics simulations with umbrella sampling techniques to elucidate the structure–interaction relationship and thermodynamics governing the penetration of polymyxins [B1 and E1 (i.e. colistin A) representing the two clinically used polymyxins] into the OM. Results: Polymyxin B1 and colistin A bound to the A. baumannii OM by the initial electrostatic interactions between the Dab residues of polymyxins and the phosphates of lipid A, competitively displacing the cations from the headgroup region of the OM. Both polymyxin B1 and colistin A formed a unique folded conformation upon approaching the hydrophobic centre of the OM, consistent with previous experimental observations. Polymyxin penetration induced reorientation of the headgroups of the OM lipids near the penetration site and caused local membrane disorganization, thereby significantly increasing membrane permeability and promoting the subsequent penetration of polymyxin molecules into the OM and periplasmic space. Conclusions: The thermodynamics governing the penetration of polymyxins through the outer leaflet of the A. baumannii OM were examined and novel structure–interaction relationship information was obtained at the atomic and membrane level. Our findings will facilitate the discovery of novel polymyxins against MDR Gram-negative pathogens.